Emerging work environments in the pandemic era: a gendered approach to work-life balance programs - Sreya, B.; Lakshmana Rao, Ayyagari; Ramakrishnan, G.; Kulshretha, Nikhil (Frontiers in Sociology, 2023)
As the coronavirus pandemic affects virtually every sector of the economy, the ongoing review examines what remote working means for women's job performance—speculations about serious activities and how they might monitor work and family. In recent years, psychometric testing has become increasingly popular with organizations worldwide, and organizations are turning to psychometrics to better understand how women achieve balance in their lives. The aim is to investigate how different aspects of psychometrics influence women's satisfaction levels, as well as factors relating to work-life balance. An exploratory factor assessment (EFA) and a confirmatory factor assessment (CFA) using a seven-point Likert scale were performed on data collected from 385 female IT workers who were selected and examined their satisfaction level towards the psychometric assessments in their organization. The results also showed that three significant variables accounted for 74% of the variance, 26% from Work and family, 24% from personal factors, and 24% from loving jobs. The current study develops and finds the key factors in the Work-Life Balance of women using EFAs and CFAs.